Evaluation of protein levels of autophagy markers (Beclin 1 and SQSTM1/p62) and phosphorylation of cyclin E in the placenta of women with preeclampsia - Akcora Yildiz, Dilara; Irtegun Kandemir, Sevgi; Agacayak, Elif; Deveci, Engin (Cellular and Molecular Biology, 2017)
Preeclampsia is a severe multisystem disorder, and its pathophysiology is still not completely understood. Autophagy, a recycling process that maintains cellular homoeostasis during differentiation and development, is controversial regarding increased or decreased autophagic activity in preeclampsia. The aim of this study was to determine whether autophagy is increased in the placentas of women with preeclampsia by examining the protein levels of autophagy markers (Beclin 1 and SQSTM1/p62) and phosphorylation of cyclin E. For this purpose, placentas from preeclampsia (n=10) and control (n=10) pregnancies were included in this study. The protein expression of autophagy-related markers Beclin1, SQSTM1/p62 and phosphorylation status of cyclin E were detected by Western blot. Our data showed that the protein levels of both Beclin 1 and SQSTM1/p62 were significantly increased, while the phosphorylation level of cyclin E was significantly decreased in placentas with preeclampsia compared to those derived from controls. The results of this study suggest that the autophagic activity is perpetually increased in preeclampsia and cyclin E protein stabilisation might be involved in the induction of autophagy.